Study of n-ZnO/ p-SiNW heterostructures grown by thermal evaporation method - Hazra P.; Jit S. (My University, 2025)
Recently SiNW (silicon nanowire) based devices have attracted great attention in the development of novel nanoelectronic devices due to their unique one-dimensional nature and associated electrical and optical properties compared to bulk silicon. In this work, n-type ZnO (Zinc Oxide) nanowire (NW) thin film was grown on p-type SiNW (silicon nanowire) arrays by simple and cost effective thermal evaporation method to obtain an n-ZnONW/ p-SiNW based heterojunction diode without using any seed layer. The SiNW arrays used for the growth of ZnONWs were developed on a p-Si wafer by using the electroless etching method. The large area ohmic contacts at top and bottom of the structure were fabricated by depositing silver and aluminium respectively. The SEM and XRD data demonstrate a good crystalline quality of the ZnONWs grown on the SiNWs. The current-voltage characteristics of the nanowire-based heterostructure device show the non-ideal diode characteristics with a high current rectification ratio of 190 and a low leakage current of 1.86×10-8 A. © 2013 AIP Publishing LLC.